The effect of high intensity rowing exercise and combined strength and endurance training on cardiovascular responses. - Bell, G.; Syratuik, D.; Haykowsky, M.; duManoir, G.; Taylor, D.
The performance of combined strength and endurance training in rowers produces significant improvements in aerobic endurance and strength as well as cardiovascular function and morphology. Thus, the combination of a volume and pressure overload to the heart as a consequence of endurance and strength training respectively, induces adaptations that contribute to improved rowing performance. Acute, high intensity rowing exercise results in a high anaerobic metabolic stress as indicated by an elevated blood lactate level after high intensity rowing exercise but this did not seem to produce any adverse effect on the function of the heart. In fact, there was an improvement in cardiovascular function after the simulated 2000 meter rowing race that was enhanced with training.